2010
DOI: 10.1016/j.otsr.2009.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Total hip arthroplasty revision due to infection: A cost analysis approach

Abstract: Level IV. Economic and decision analyses, retrospective study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
148
0
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(190 citation statements)
references
References 2 publications
1
148
0
10
Order By: Relevance
“…Treatment failures are not only costly, but also are associated with substantial morbidity and mortality [1,3,6,8,12] Although two-stage exchange arthroplasty remains a commonly used treatment approach, it remains imperfect. Studies have reported success rates approaching 90%, whereas others have reported less successful outcomes [7].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment failures are not only costly, but also are associated with substantial morbidity and mortality [1,3,6,8,12] Although two-stage exchange arthroplasty remains a commonly used treatment approach, it remains imperfect. Studies have reported success rates approaching 90%, whereas others have reported less successful outcomes [7].…”
Section: Discussionmentioning
confidence: 99%
“…A recent cost-analysis study in France found that costs of septic revisions were 3.6 times higher following a THA than following a primary THA, mainly because of longer hospitalisation periods and rehabilitation after hospital discharge. 41 The treatment or revision of an infected joint can be very time-consuming and resource intensive. 42,43 Costs of SSIs usually increase with the depth of infection (i.e.…”
Section: Permanent Resectionmentioning
confidence: 99%
“…38 The economic burden of SSI after hip arthroplasty was reported to increase health-care costs by more than 300%, but dollar estimates differ widely, from US$400 to US$60,000 per SSI treated. 5,38,41,44,45 Apart from obvious reasons for the wide range of estimated costs, such as severity of infection or differing hospital fees in different countries, there is no consistent methodology used to calculate costs of infection. 46 The measurement of cost requires identifying the quantity of resource use and the unit costs or prices for using the resources.…”
Section: Permanent Resectionmentioning
confidence: 99%
“…However, there has been a lack of consensus on the type of spacer that should be implanted, as well as the antibiotic and its concentration that should be incorporated into these spacers. The infection control rates that have been associated with the various types of available spacers and their indications need to be defined in order to help maximize rates of infection control, while minimizing cost and hospitalization lengths [10].…”
Section: Introductionmentioning
confidence: 99%